The Tracking of Palakesimpar Lexicon in The Javanese Language - Sri Nardiati; Suyami Suyami (International Journal of Science and Applied Science: Conference Series, 2022)
Palakesimpar lexicon had a great benefit, especially for people’s health. Besides that, this research was believed to have the value of local wisdom, which had a large enough contribution to developing the Indonesian language The aims of this research were to 1) determine the palakesimpar lexicon in the Javanese language; 2) classify the lexicons based on their function; 3) describe the cultural meaning and philosophy which was available behind the palakesimpar lexicon. Ethnolinguistics theory with a qualitative approach was used in this research. As a qualitative approach, this research used ethnolinguistic theory which was supported by the symbolic interaction theory. Data obtained from three sources include humans as informants, references or documents, and circumstances or events. Pieces of information obtained from the informants later were typed as writing which will form the words, phrases, sentences, sentences cluster, or text. The result of the research could find that palakesimpar lexicons consist of 28 units. They can be categorized according to their function in life as 1) vegetables, 2) fruits, 3) snacks, and 4) drugs. There were 13 kinds of vegetables, namely bligo, blestru, gambas, jipang, labu, kara benguk, kara buncis, kara krupuk, kara uceng, kacang gleyor, kacang tholo, kacang ruji, and kacang kapri. There were 8 types of fruits:  blewah, krai, markisa, melon, semangka, timun, timun wuku, and timun suri. There were 2 types of snacks: wuluh and bligo. The last, there were 3 kinds of drugs: cabe, mrica, and kemukus. Based on the analysis, it was known that palakesimpar lexicons had 28 units categorized as thukulan, not tandurans ‘plant’. The other lexical units worked as fruits, snacks, and drugs. For Javanese people, some of the palakesimpar lexicons can build the idiomatic expression. They had indirect meanings. The meaning of indirect meaning could be understood through context by applying the translation technique which was correlated with philosophical values in Javanese culture. The object of study that applies ethnolinguistics theory is still limited in number. There are many topics that have not been studied yet. For this reason, more adequate research both in terms of quantity and quality needs to be carried out. It is very important because, by this anthropological linguistic theory, the values of the cultural philosophy contained behind the use of language can be revealed.